183k views
1 vote
Consider the expression 25 – 10 ÷ 2 + 3.

Part A
Which shows a way to rewrite the expression using parentheses so that the expression equals 23?
Select all that apply.
A. (25 – 10) ÷ 2 + 3 = 23
B. 25 – 10 ÷ (2 + 3) = 23
C. (25 – 10) ÷ (2 + 3) = 23
D. 25 – (10 ÷ 2) + 3 = 23
Part B
Which shows a way to rewrite the expression using parentheses so that the expression equals 3?
A. (25 – 10) ÷ 2 + 3 = 3
B. 25 – 10 ÷ (2 + 3) = 3
C. (25 – 10) ÷ (2 + 3) = 3
D. 25 – (10 ÷ 2) + 3 = 3

User Skan
by
5.3k points

1 Answer

3 votes

Given:

The expression is:


25-10/ 2+3

To find:

Part A: The expression using parentheses so that the expression equals 23.

Part B: The expression using parentheses so that the expression equals 3.

Solution:

Part A:

In option A,


(25-10)/ 2+3=15/ 2+3


(25-10)/ 2+3=7.5+3 [Using BODMAS]


(25-10)/ 2+3=10.5

In option B,


25-10/ (2+3)=25-10/ 5


25-10/ (2+3)=25-2 [Using BODMAS]


25-10/ (2+3)=23

In option C,


(25-10)/ (2+3)=15/ 5


(25-10)/ (2+3)=3

In option D,


25-(10/ 2)+3=25-5+3


25-(10/ 2)+3=28-5 [Using BODMAS]


25-(10/ 2)+3=23

After the calculation, we have
25-10/ (2+3)=23 and
25-(10/ 2)+3=23.

Therefore, the correct options are B and D.

Part B: From part A, it is clear that


(25-10)/ (2+3)=3

Therefore, the correct option is C.

User Sagar Waghmare
by
5.2k points